Astragaloside IV Exerts Cognitive Benefits and Promotes Hippocampal Neurogenesis in Stroke Mice by Downregulating Interleukin-17 Expression via Wnt Pathway - Sun, Li; Zhang, Heming; Wang, Wen; Chen, Zhiyang; Wang, Shuang; Li, Jiangjing; Li, Guangyao; Gao, Changjun; Sun, Xude (Frontiers in Pharmacology, 2020)
Background: Stroke remains a leading cause of adult disability and the demand for stroke rehabilitation services is growing, and Astragaloside IV (As IV), a primary bioactive compound of Radix Astragali, may be a promising stroke therapy. Methods: To access the effect of As IV on adult mice after ischemic stroke, a photochemical ischemia model was established on C57BL/6 mice, which were intravenously administered As IV for three consecutive days later. And then the cognitive benefits and hippocampal neurogenesis were evaluated by Morris Water Maze (MWM) test, Golgi staining, immunohistochemical staining in vivo and in vitro. Furthermore, to find out the underlying mechanism, interleukin-17 (IL-17) knock out (KO) mice were used, through RNA sequence (RNA-seq) analysis and immunohistochemistry. Then the mechanism of neurogenesis promoted by As IV was observed by western blot both in vivo and in vitro. Specifically, As IV, recombinant mouse IL-17A and IL-17F, and Wingless/integrated (Wnt)-expressing virus was administered respectively in neural stem cells (NSCs), and then their diameters and protein expression of Nestin, IL-17 and Wnt pathway relevant protein, were measured in vitro. Results: Administering As IV resulted in significant amelioration of stroke-induced cognitive deficits. And more hippocampal neurons with normal morphology, significant increments in the length of the apical dendrites and the density of their spines were observed in As IV-treated mice. Furthermore, the immunohistochemistry staining of DCX/BrdU, and Sox2 /Nestin showed As IV could promote hippocampal neurogenesis and NSC proliferation after ischemic stroke, as well as in vitro. For the mechanism underlying, IL-17 expression was downregulated significantly by As IV treatment and knocking out IL-17 was associated with nervous regeneration and synapse repair according to the analysis of RNA-seq. Consistent to As IV treatment, knocking out IL-17 showed some promotion on hippocampal neurogenesis and proliferation of NSCs, with activating Wnt pathway after stoke. Finally, in vitro, NSCs’ diameters and protein expression of Nestin, IL-17 and Wnt pathway were regulated by either administering As IV or inhibiting IL-17. Conclusion: As IV stimulates hippocampal neurogenesis after stroke, thus potentially facilitates brain to remodel and repair by downregulating IL-17 expression via Wnt pathway.